Identification and calibration of one-way delays in satellite laser ranging systems. Issue 10 (15th May 2017) - Prochazka, Ivan; Kodet, Jan; Blazej, Josef; Kirchner, Georg; Koidl, Franz; Wang, Peiyuan
Highlights: A calibration of one-way system delays in satellite laser ranging systems. A new procedure for laser time transfer ground to space and for bi- and multi-static laser ranging to space objects. Experimental results demonstrate signal propagation delays calibration with an accuracy of better than 20 ps. Abstract: We are reporting on identification and calibration of one-way delays in satellite laser ranging systems. Satellite Laser Ranging (SLR) is a standard technique to measure the distance of satellites as a function of time with millimeter precision and a few millimeters accuracy. For one-way laser ranging, laser time transfer ground to space and for bi- and multi-static laser ranging to space objects identification and measurement of system delays related separately to transmitting and receiving parts of the system are needed. The epochs of transmission and reception of optical signals have to be referred to the coordinated time scale with the accuracy reaching one nanosecond level or better for one-way ranging and space debris multi-static ranging. For transponder ranging and laser time transfer an even higher accuracy of 50 ps or better is needed. These accuracy requirements are by several orders of magnitude higher in comparison to standard SLR applications. A new procedure of calibration of one-way delays related to the SLR systems has been developed and tested. The necessary hardware components needed for calibration measurements were designed and developed in a form of a Calibration Device. It consists of a photon counting detector, an epoch timing device and a dedicated signal cable. The signal propagation delays of these components were determined with an accuracy of better than 20 ps. The signal propagation delay stability of the Calibration Device is on a level of units of picoseconds over days of operation. The Calibration Device and calibration procedure were tested in real measurements at the SLR site in Graz, Austria. The time needed to complete a calibration of one-way delays of the SLR system is less than two days. The one-way system delays were determined with the accuracy better than 50 ps. The measurement principle, Calibration Device and the first results are presented.